Florbetapir PET, FDG PET, and MRI in Down syndrome individuals with and without Alzheimer's dementia. Issue 8 (4th April 2015) - Sabbagh, Marwan N.; Chen, Kewei; Rogers, Joseph; Fleisher, Adam S.; Liebsack, Carolyn; Bandy, Dan; Belden, Christine; Protas, Hillary; Thiyyagura, Pradeep; Liu, Xiaofen; Roontiva, Auttawut; Luo, Ji; et al.
Abstract: Introduction: Down syndrome (DS) is associated with amyloid b (Ab) deposition. Methods: We characterized imaging measurements of regional fibrillar Ab burden, cerebral metabolic rate for glucose (rCMRgl), gray matter volumes (rGMVs), and age associations in 5 DS with dementia (DS/AD1), 12 DS without dementia (DS/AD2), and 9 normal controls (NCs). Results: There were significant group differences in mean standard uptake value ratios (SUVRs) for florbetapir with DS/AD1 having the highest, followed by DS/AD2, followed by NC. For [18F]‐fluorodeoxyglucose positron emission tomography, posterior cingulate rCMRgl in DS/AD1 was significantly reduced compared with DS/AD2 and NC. For volumetric magnetic resonance imaging (vMRI), hippocampal volumes were significantly reduced for the DS/AD1 compared with DS/AD2 and NC. Age‐related SUVR increases and rCMRgl reductions were greater in DS participants than in NCs. Discussion: DS is associated with fibrillar Ab, rCMRgl, and rGMV alterations in the dementia stage and before the presence of clinical decline. This study provides a foundation for the studies needed to inform treatment and prevention in DS.